ATRIBUT DAN URUTAN PRIORITAS KEBUTUHAN KONSUMEN DALAM PERANCANGAN COOKIES BEBAS GLUTEN DARI TEPUNG JAGUNG - Aini, Nur; Sustriawan, Budi; Arista, Lintang; Mela, Ervina; Arsyistawa, Hadana Sabila (Jurnal Agroindustri, 2023)
Cookies are snacks that are popular among the public, whose main raw material is generally wheat flour. The process of making cookies does not require flour with a high gluten content so that in the manufacturing process wheat flour can be replaced, and as an alternative is corn flour. The aim of the research is to determine the consumer attributes that influence the development of corn cookies products, to find out the technical parameters that affect the development of corn cookies products and to know the priority of consumer requirements and technical parameters that must be met in the development of corn cookies products. The research took place in several stages, namely identifying the attributes of consumer requirements by distributing questionnaires, identifying technical parameters by studying the literature, determining priority attributes of consumer requirements and prioritizing technical parameters. Determining the number of respondents was carried out using the proportion method for the population aged 18-45 years who live in Purwokerto City who like cookies. Questionnaires were distributed to 100 respondents to identify consumer requirements, product design specifications, level of importance, satisfaction, and attractiveness. Data analysis is carried out through cumulative calculations to fulfil consumer desires based on consumer requirements and technical parameters to produce a House of Quality (HOQ). The results showed that in the development of corn cookies there were 14 important parameters, namely raw materials, product formulation, mixing time, the order in which the ingredients were added during mixing, molding shape, baking temperature, baking time, packaging, labelling, quality checking (Quality Control), PIRT registration, Halal registration, storage, and BPOM registration. The three highest priority attributes of consumer requirements are the label design on the product that describes the product content (8.38%), has a distinctive cookie aroma (8.23%) and the packaging label includes the ingredient composition (8.12%).